213k views
5 votes
Solve

(X^2+2xy+y^2)(x+1)

Solve (X^2+2xy+y^2)(x+1)-example-1
User Kwart
by
5.1k points

1 Answer

4 votes

Answer:

x = -1 or x = -y

Explanation:

Solve for x:

(x + 1) (x^2 + 2 x y + y^2) = 0

Split into two equations:

x + 1 = 0 or x^2 + 2 x y + y^2 = 0

Subtract 1 from both sides:

x = -1 or x^2 + 2 x y + y^2 = 0

Write the left hand side as a square:

x = -1 or (x + y)^2 = 0

Take the square root of both sides:

x = -1 or x + y = 0

Subtract y from both sides:

Answer: x = -1 or x = -y

User Youn Elan
by
5.6k points